Experience of mTBI-Like Symptoms in a Sample Without Brain Injury in Aotearoa/New Zealand - Chua, Jason; Theadom, Alice (CSIRO Publishing, 2024)
Background Post-mild traumatic brain injury (mTBI) symptoms are not specific to mTBI and are experienced in populations without brain injury. Understanding how people without brain injury experience mTBI-like symptoms and factors influencing symptom reporting is important to determine how symptom experience differs following an mTBI. Methods To understand how people without a history of brain injury experience mTBI-like symptoms, we conducted a cross-sectional survey comprising sociodemographic characteristics, the Brain Injury Screening Tool symptom scale, general health rating, Illness Attitude Scale, Positive and Negative Affect Scale and Perceived Stress Scale. The mean total symptom score and proportion of people experiencing moderate or severe symptoms (≥4) were reported. Associations between sociodemographic variables, stress, negative affect, illness attitudes, health status and symptoms were examined using regression models. Results One-hundred and seventy-three people completed the survey with a mean age of 40 years (s.d. = 15.8; n = 82, 47.4% male). The mean total symptom score was 34.5( ± 26.6). Commonly experienced symptoms were tiredness (n = 73, 42.2%), poor sleep (n = 64, 37.0%) and headaches (n = 56, 32.4%). Regression analysis revealed that on average higher levels of worry about illness and negative affect were associated with higher symptoms (β = 0.5, P = 0.027 and β = 0.9, P = 0.020 respectively) but there were no significant associations with other variables. Conclusions Cognitive and vestibular-ocular symptoms occur much less frequently than physical symptoms in the general population and may be more specific to mTBI. However, there is a need to consider vestibular-ocular symptoms alongside illness attitudes due to greater concerns about these symptoms by patients.
Keywords: 5203 Clinical and Health Psychology; 4203 Health Services and Systems; 42 Health Sciences; 52 Psychology; Eye Disease and Disorders of Vision; Brain Disorders; Physical Injury - Accidents and Adverse Effects; Traumatic Brain Injury (TBI); Traumatic Head and Spine Injury; Clinical Research; Neurosciences; Behavioral and Social Science; 3 Good Health and Well Being; 11 Medical and Health Sciences; 17 Psychology and Cognitive Sciences; 32 Biomedical and clinical sciences; 42 Health sciences; 52 Psychology